Fighting for faith and nation : dialogues with Sikh militants - Mahmood, Cynthia Keppley (Series in contemporary ethnography., 1997)
"A stunning presentation of narrative ethnography, achieving the remarkable feat of forcing the reader to enter into the world-and the world view-of those whom most of us would regard as terrorists."--Mark Juergensmeyer, UCSB